A study on market interdependence of futures markets with its underlying assets: analysis on Latin America Developed & Emerging Market (Canada, Mexico and United State) / Nurul Hidayah Hamid - Hamid, Nurul Hidayah (2011)
There are many research have been conduct in order to investigate the relationship between spot and futures market in Latin America region. The objective of the investigation is to identify the market interdependence relationship between the futures and spot market in the Latin America which is Canada, Mexico and United State. The study use Single Linear regression Model in order to find the relationship among stock market index and to describe the relationship between a single dependent variable y and a single independent variable x. The Canada use S&P 60 Index, IPC stock index is from Mexico country while United State use S&P 500 stock Index for the spot and futures Market. The weekly closing price of stock index and weekly settlement price from 1st January 2005 until 31st December 2010 are collected from the data stream. The result shows that there is bidirectional relationship between Canada stock Market, Mexico stock market and United State stock market. Furthermore, the result also evidence that there are significance relationship between spot and futures index in three of the country Canada, Mexico and United State. On the other hand, the result from this study has some potential to be used by the market analyst for predicting country market movement and also useful to regulators of stock markets in regulating policies to control the price relationship between those markets.